The Effects of the Ketogenic Diet on Disorders of Central Nervous System - Mikołajec, Patryk; Jolanta Mędyk; Michał Rogulski; Yauheniya Patarocha; Aleksandra Ślusarska; Paulina Błasiak; Małgorzata Wirkijowska; Ruslan Huk; Barbara Bilecka (Journal of Education, Health and Sport, 2025)
The ketogenic diet (KD) that focuses on forcing body to switch from burning glucose to burning fat for fuel, has recently been a subject of livid investigation in terms of being a viable therapeutic option for various disorders, starting with obesity, through neurological and neurodevelopmental disorders, to mental disorders such as schizophrenia. Emerging evidence suggests that it may be useful in treating these conditions. This article explores the possible role of KD in the treatment of those condition. Methods: Extensive research was conducted using PubMed and Google Scholar. References from selected articles were included in the analysis.